Exenatide at therapeutic and supratherapeutic concentrations does not prolong the QTc interval in healthy subjects - Darpö, Börje; Philip, Sager; MacConell, Leigh; Cirincione, Brenda; Mitchell, Malcolm; Han, Jenny; Huang, Wenying; Malloy, Jaret; Schulteis, Christine; Shen, Larry; Porter, Lisa (British journal of clinical pharmacology, 2013)
Aims Exenatide has been demonstrated to improve glycaemic control in patients with type 2 diabetes, with no effect on heart rate corrected QT (QTc) at therapeutic concentrations. This randomized, placebo‐ and positive‐controlled, crossover, thorough QT study evaluated the effects of therapeutic and supratherapeutic exenatide concentrations on QTc. Methods Intravenous infusion was employed to achieve steady‐state supratherapeutic concentrations in healthy subjects within a reasonable duration (i.e. days). Subjects received exenatide, placebo and moxifloxacin, with ECGs recorded pre‐therapy and during treatment. Intravenous exenatide was expected to increase heart rate to a greater extent than subcutaneous twice daily or once weekly formulations. To assure proper heart rate correction, a wide range of baseline heart rates was assessed and prospectively defined methodology was applied to determine the optimal QT correction. Results Targeted steady‐state plasma exenatide concentrations were exceeded (geometric mean ± SEM 253 ± 8.5 pg ml−1, 399 ± 11.9 pg ml−1 and 627 ± 21.2 pg ml−1). QTcP, a population‐based method, was identified as the most appropriate heart rate correction and was prespecified for primary analysis. The upper bound of the two‐sided 90% confidence interval for placebo‐corrected, baseline‐adjusted QTcP (ΔΔQTcP) was <10 ms at all time points and exenatide concentrations. The mean of three measures assessed at the highest steady‐state plasma exenatide concentration of ∼500 pg ml−1 (ΔΔQTcPavg) was −1.13 [−2.11, −0.15). No correlation was observed between ΔΔQTcP and exenatide concentration. Assay sensitivity was confirmed with moxifloxacin. Conclusions These results demonstrated that exenatide, at supratherapeutic concentrations, does not prolong QTc and provide an example of methodology for QT assessment of drugs with an inherent heart rate effect.